Autonomic activity and its relationship with the endogenous cardiotonic steroid marinobufagenin: the African-PREDICT study. (1st November 2020) - Strauss, Michél; Smith, Wayne; Wei, Wen; Fedorova, Olga V.; Schutte, Aletta E.
ABSTRACT: Aim: Marinobufagenin (MBG), a cardiotonic steroid and a natriuretic hormone, is elevated in response to high salt diet consumption. In animal models salt intake stimulates adrenocortical MBG secretion via increased angiotensin II, sympathetic activity and aldosterone. No evidence in humans exists to suggest the involvement of the angiotensinergic-sympatho-excitatory pathway in MBG production. We investigated whether MBG is related to indices of autonomic activity in men and women. Methods: This cross-sectional study included 680 black and white, men and women from the African-PREDICT study (aged 20–30 years). Continuous 24 hr ECG recordings were used to obtain low and high frequency (LF, HF) heart rate variability (HRV). We measured 24 hr urinary MBG excretion and serum aldosterone. Results: We found a positive association of MBG excretion with estimated salt intake ( P  < 0.001) and aldosterone ( P  < 0.001) in women and men. In women only, a positive relationship was evident between MBG excretion and LF HRV in multivariate adjusted regression analyses (Adj. R 2  = 0.33; β  = 0.11; P  = 0.030). In men, MBG excretion associated positively with HF HRV in similar regression analyses ( R 2  = 0.36; β  = 0.12; P  = 0.034). Sex-specific results were corroborated only in blacks, namely, a positive association of MBG excretion with LF HRV in black women ( R 2  = 0.38; β  = 0.13; P  = 0.036), and negative association with HF HRV in black men ( R 2  = 0.40; β  = 0.18; P  = 0.045). No relationships were evident in white women ( P  = 0.58) or men ( P  = 0.27). Conclusion: Our findings in this human cohort support suggested mechanisms whereby MBG is elevated as a result of increased salt intake, including autonomic activity, previously demonstrated in Dahl salt-sensitive hypertension.